Prognostic relevance of arrhythmic and QTc burden in takotsubo cardiomyopathy: A systematic review and meta‐analysis - Ankit Hanmandlu; Jyothik Varun Inampudi; Mohammad Hamza; Prakash Upreti; Abdul Rasheed Bahar; Jawad Basit; Sivaram Neppala; Himaja Dutt Chigurupati; Rohit Goru; M. Chadi Alraies (Journal of Arrhythmia)
Abstract Introduction Takotsubo cardiomyopathy is characterized by stress‐induced systolic dysfunction of the left ventricle that is largely reversible and not related to coronary ischemia. Patients with Takotsubo cardiomyopathy can often develop concurrent arrhythmias and prolonged QTc interval, which have been shown to contribute to significant morbidity and mortality in prior retrospective studies. Hence, we conducted a comprehensive systematic review and meta‐analysis to characterize the risk of atrial arrhythmias, life‐threatening arrhythmias, and QTc prolongation on clinical outcomes in patients with Takotsubo cardiomyopathy. Methods We searched PubMed and EMBASE databases from inception to April 2024. A total of 13 studies were eligible for data collection across the three subgroups. Results Atrial and life‐threatening arrhythmias in Takotsubo cardiomyopathy have an increased risk of in‐hospital mortality and cardiogenic shock, a finding that was not observed in patients with prolonged QTc. Upon univariate analysis of the QTc subgroup, younger age and the presence of ST‐Elevation were identified as additional negative prognostic indicators of adverse outcomes in Takotsubo cardiomyopathy. Conclusion Our study demonstrates the increased risk of different arrhythmic profiles in Takotsubo cardiomyopathy. Further investigation is needed to identify pathophysiological mechanisms and tailored anti‐arrhythmics to improve outcomes in this unique subset of Takotsubo patients.